Suatu tinjauan mengenai minat membaca dan bahan-bahan yang dibaca oleh pelajar-pelajar sekolah menengah desa di Semenanjung Malaysia - Hashim, Mohd Zainuddin (1982)
The aim of this survey research is to extract information about the reading interest of and the materials used by rural secondary school student sin Peninsular Malaysia. The districts of Larut and Matang, Selama, and Kerian have been selected as a sampling area. The sampling unit is the school and the survey questionaire has been administered to 500 student s from five selected schools, according to stratified random sampling procedure. This stratified random sampling design has been an attempt to examine, besides other variables, the probable functional relationship between reading interests and the materials the rural students read as well as library utilization. xiv The findings reveal that the students read regularly for examinations and their reading tend to be confined to text books. Rural student s also read more of reading materials in Bahasa Malaysia than in any other languages.